MiR-29a Suppresses Spermatogenic Cell Apoptosis in Testicular Ischemia-Reperfusion Injury by Targeting TRPV4 Channels - Ning, Jin-zhuo; Li, Wei; Cheng, Fan; Yu, Wei-min; Rao, Ting; Ruan, Yuan; Yuan, Run; Zhang, Xiao-bin; Zhuo, Dong; Du, Yang; Xiao, Cheng-cheng (Frontiers in Physiology, 2017)
Background: MicroRNAs (miRNAs) have emerged as gene expression regulators in the progression of ischemia-reperfusion injury (IRI). MiR-29a has been reported to play key roles in myocardial and cerebral IRI. However, the role of miR-29a in testicular IRI has not been fully elucidated. Methods: Changes in expression of miR-29a and Transient Receptor Potential Vanilloid 4 (TRPV4) in animal samples and GC-1 spermatogenic cells were examined. The effects of miR-29a on spermatogenic cell apoptosis in testicular IRI were analyzed both in vitro and in vivo. Results: The expression of MiR-29a was negatively correlated with the expression of TRPV4 and significantly downregulated in animal samples and GC-1 cells as testicular IRI progressed. Further studies identified TRPV4 as a direct target of miR-29a. Inhibition of miR-29a expression increased the expression of TRPV4 and promoted spermatogenic cell apoptosis, whereas overexpression of miR-29a downregulated TRPV4 expression and suppressed spermatogenic cell apoptosis caused by testicular IRI in vitro and in vivo. Conclusion: Our results suggest that miR-29a suppresses apoptosis induced by testicular IRI by directly targeting TRPV4.